Pengaruh Pengendalian Internal, Good Governance, dan Ketaatan Standar Akuntansi Terhadap Kecenderungan Fraud - Anabela Triyana (Pascasarjana Universitas Sultan Ageng Tirtayas, 2025)
Fraud remains a serious problem in government, including in regional government work units that manage the state budget. This study aims to determine the effect of internal control, good governance, and compliance with accounting standards on the likelihood of fraud. This study uses a quantitative method with a descriptive approach. The study population was work units under the jurisdiction of the Kantor Pelayanan Perbendaharaan Negara (KPPN) in Bandung City. The sampling technique used was purposive sampling. The results show that, partially, internal control and good governance do not affect the likelihood of fraud. Conversely, compliance with accounting standards does affect the likelihood of fraud. However, simultaneously, all three variables have a significant effect on the likelihood of fraud.